Rancang Bangun Aplikasi J-Cashier Mobile - Jakkirahman , Jakkirahman; Nugrahaningsih, Nahumi (Journal of Information Technology and Computer Science, 2022)
J-Cashier Mobile is an application in the form of a mobile cashier with features for calculating change, recording transactions, and send reports to the email of BUMDes owners. The design of this application aims to facilitate the management and development of BUMDes in the form of applications that can manage transactions and can record transactions that have taken place.